Blunted increases in skin sympathetic nerve activity are related to attenuated reflex vasodilation in aged human skin - Stanhewicz, Anna E. (J Appl Physiol (1985), 2016)
Reflex cutaneous vasodilation in response to passive heating is attenuated in human aging. This diminished response is mediated, in part, by age-associated reductions in endothelial function; however, the contribution of altered skin sympathetic nervous system activity (SSNA) is unknown. We hypothesized that 1) healthy older adults would demonstrate blunted SSNA responses to increased core temperature compared with young adults and 2) the decreased SSNA response would be associated with attenuated cutaneous vasodilation. Reflex vasodilation was elicited in 13 young [23 ± 1 (SE) yr] and 13 older (67 ± 2 yr) adults using a water-perfused suit to elevate esophageal temperature by 1.0°C. SSNA (peroneal microneurography) and red cell flux (laser Doppler flowmetry) in the innervated dermatome (the dorsum of foot) were continuously measured. SSNA was normalized to, and expressed as, a percentage of baseline. Cutaneous vascular conductance (CVC) was calculated as flux/mean arterial pressure and expressed as a percentage of maximal CVC (local heating, 43°C). Reflex vasodilation was attenuated in older adults (P < 0.001). During heating, SSNA increased in both groups (P < 0.05); however, the response was significantly blunted in older adults (P = 0.01). The increase in SSNA during heating was linearly related to cutaneous vasodilation in both young (R(2) = 0.87 ± 0.02, P < 0.01) and older (R(2) = 0.76 ± 0.05, P < 0.01) adults; however, slope of the linear regression between ΔSSNA and ΔCVC was reduced in older compared with young (older: 0.05 ± 0.01 vs. young: 0.08 ± 0.01; P < 0.05). These data demonstrate that age-related impairments in reflex cutaneous vasodilation are mediated, in part, by blunted efferent SSNA during hyperthermia.